Edukasi Pembelajaran Saintifik Pada Guru-Guru Madrasah Ibtidaiyah As Shofa - Siti Nursyamsiyah; Toni Herlambang (Journal of Community Development, 2023)
Scientific learning is entrusted learning from the K-13 curriculum which includes the 5 Ms, namely (observing, asking, reasoning, communicating and presenting). Scientific learning education was attended by 12 teachers from various subject areas. This learning model is very important to be implemented in schools with the aim of building a critical attitude of students, learning becomes conducive and harmonious, motivating and encouraging students to communicate. Scientific learning education for MI As Shofa teachers is the main goal to provide changes in everyday learning. The method of implementing this service uses demonstrations related to scientific designs. Assistance in the preparation of the learning framework is carried out with the implementing team and evaluating the results. The results of this implementation show the motivation and enthusiasm of teachers in socialization activities and the responses of teachers in observing media images and being able to provide appropriate responses. At the end of the implementation, the teachers designed lesson plans for each subject using a scientific approach that applied the 5 M.